X-ray properties of z ≳ 6.5 quasars. Issue 3 (22nd November 2019) - Pons, E; McMahon, R G; Banerji, M; Reed, S L
ABSTRACT: We present XMM–Newton X-ray observations and analysis of three Dark Energy Survey z > 6.5 quasars (VDES J0020−3653 at z = 6.824, VDES J0244−5008 at z = 6.724, and VDES J0224−4711 at z = 6.526) and six other quasars with 6.438 < z < 6.747 from the XMM–Newton public archive. Two of the nine quasars are detected at a high (>4σ) significance level: VDES J0224−4711( z = 6.53) at 9σ and PSO J159−02 ( z = 6.38) at 8σ. They have a photon index of Γ =1.82^+0.29_-0.27 and 1.94^+0.31_-0.29, respectively, which is consistent with the mean value of ∼1.9 found for quasars at all redshifts. The rest-frame 2–10 keV luminosity of VDES J0224−4711 is L_2\!-\!10 keV = (2.92± 0.43)× 10^45 erg s^-1, which makes this quasar one of the most X-ray luminous quasars at z > 5.5 and the most X-ray luminous quasar at z > 6.5, with a luminosity 6 times and 2.5 times larger than ULAS J1120+0641 ( z = 7.08) and ULAS J1342+0928 ( z = 7.54), respectively. The X-ray-to-optical power-law slopes of the nine quasars are consistent with the previously observed anticorrelation of αox with UV luminosity L_2500 A . We find no evidence for evolution of αox with redshift when the anticorrelation with UV luminosity is taken into account. Similar to previous studies at z ∼ 6, we have found remarkably consistent X-ray spectral properties between low-redshift quasars ( z ∼ 1) and high-redshift quasars. Our results add further evidence to the picture that the observable properties of high-luminosity quasars over the UV-to-X-ray spectral region have not evolved significantly from z ∼ 7 to the present day and that quasars comparable to local versions existed 800 Myr after the big bang.